2002
DOI: 10.1063/1.1455616
|View full text |Cite
|
Sign up to set email alerts
|

Structural, magnetic, and thermal stability of IrMn exchange biased layers

Abstract: The magnetic domain structure, magnetic properties, and thermal stability of IrMn biased top spin valves containing Co and NiFe have been investigated. The magneto-optical indicator film pictures of Ni–Fe biased IrMn spin valve show the formation and motion of domain walls that separate large domains in the free film unlike the Co biased IrMn spin valve structure with many small microdomains. From the angular dependence of the ferromagnetic resonance linewidth (ΔH) and resonance field (Hres) it was found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
8
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…One can see that up to T ANN ¼ 360 C the shape of the loops is nearly unchanged, but the maximum MR ratio has decreased significantly. The MR ratio maximums decreased rapidly following annealing above 260 C [5]. Despite the large changes in MR ratio, the H EX (B30 T) and H C (B4.5 mT) values were essentially unchanged at for each T ANN : The loop shape after a 390 C anneal (Fig.…”
mentioning
confidence: 85%
See 4 more Smart Citations
“…One can see that up to T ANN ¼ 360 C the shape of the loops is nearly unchanged, but the maximum MR ratio has decreased significantly. The MR ratio maximums decreased rapidly following annealing above 260 C [5]. Despite the large changes in MR ratio, the H EX (B30 T) and H C (B4.5 mT) values were essentially unchanged at for each T ANN : The loop shape after a 390 C anneal (Fig.…”
mentioning
confidence: 85%
“…In recent publications, [1][2][3][4][5][6], it was revealed that diffusion of constituent atoms such as Mn and Ni over the existing layers during annealing results in a decrease of the GMR. In the present work, we report on domain imaging studies of the effects of annealing on the spinvalves (SVs) magnetic domain structure and magnetization reversal process as well.…”
mentioning
confidence: 99%
See 3 more Smart Citations